No Time Like the Present: Thinking About the Past and the Future Is Related to State Dissociation Among Individuals With High Levels of Psychopathological Symptoms - Vannikov-Lugassi, Miriam; Soffer-Dudek, Nirit (Frontiers in Psychology, 2018)
Several short-term pathways have been implicated in relation to dissociative experiences, among them are daily stress, sleepiness, and rumination. In addition, it has been claimed that mechanisms contributing to dissociative experiences may differ, according to specific psychopathological symptoms. Accordingly, this study had two aims. The first was to sample moment-to-moment increases or decreases in current stress, sleepiness, and rumination, in order to assess their temporal relations with state dissociation. Rumination was broken down to its basic two subcomponents: the negative value of the thoughts and thinking about the past (in comparison to present or future), in order to differentiate it from other repetitive thought patterns (e.g., worry). The second goal was to explore whether depression, anxiety, and obsessive-compulsive symptoms may moderate the links between the three mechanisms and specific state dissociation scales (specifically, depersonalization-derealization (DEP-DER) and absorption (ABS)). Ninety-nine undergraduate students completed trait questionnaires and then answered state items four times a day for four days. These experience sampling data were analyzed using multilevel linear modeling (MLM) with Level 1 state measurements and Level 2 demographic and trait variables of the participants. Moments of stress, sleepiness, thinking about the past and negative thoughts were all associated both with state DEP-DER and with state ABS. Dissociation, negative thinking, stress, and sleepiness were positively associated with moments of thinking about the past and the future but inversely associated with moments of thinking about the present. Finally, in accordance with our expectations, the links between DEP-DER and hypothesized mechanisms were mostly moderated by depression and anxiety symptoms, whereas the links between ABS and hypothesized mechanisms were moderated mainly by obsessive-compulsive symptoms. Our findings are in accordance with literature on the efficacy of mindfulness as well as the maladaptive correlates of mind-wandering, as they suggest that dissociative detachment from one’s present occupation is associated with decreased well-being.